Fenomena Keterkaitan Kecepatan Faktual Kendaraan dengan Tingkat Pelayanan Jalan (Studi Kasus: Jalan Asrikaton, Kabupaten Malang) - Adibah, Amalia Nur; Abadi, Khoirul; Amal, Andi Syaiful; Darmawan, Azhar Adi; Sunarto, Sunarto (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Asrikaton street, Pakis, Malang Regency is one of the roads with moderate population density and moderate traffic flow conditions. This road is classified as a secondary arterial road and is a border road with Malang City. This road has a length of 1,200 m and a pavement width of 9 meters, with a road type of two undivided lanes (2/2 UD). This study aims to observe and assess the phenomenon of the relevance between the degree of saturation and various types of light vehicle speeds of a road. The traffic volume is 6436 vehicles/hour with a low side obstacle classification, and the degree of saturation shows that the road conditions are still relatively smooth. The maximum traffic flow volume of 2039.95 smp/h occurred at 06:45-07:45 WIB. with a low side obstacle class (equivalent value 198.7), resulting in a degree of saturation of 0.66. The most significant relevance between degree of saturation and vehicle movement speed is journey speed with the equation y = -1196.9x3 + 2008.6x2 - 1095.1x + 234.37, the coefficient of determination of 0.8867.